Pemanfaatan Potensi Sumber Daya Lokal melalui Produksi Biopestisida Nabati dalam Mewujudkan Kemandirian Petani dan Pertanian Ramah Lingkungan di Desa Gumelar - Muhamad Baedowi; Afik Solihudin; Bagja; Shakiyah Alfaizah; Muhamad Wildan Zein; Indah Hayati Ayatillah; Anindya Kartika Putri; Khoerul Amalia Ramadhani; Balqis Salsabila Shafa; Najwa Keisya Rachman; Ferissa Annida Ramadhini; Adeyunita Rachmadhani; Maulana, Bagja (Abdi Jaya : Jurnal Pengabdian Indonesia, 2026)
The agricultural sector in Indonesia heavily relies on chemical pesticides, causing environmental degradation, ecosystem imbalance, and health risks for farmers. Gumelar Village in Wonosobo Regency faces similar challenges, where farmers depend on synthetic pesticides due to limited knowledge of safer alternatives. This community service activity aimed to provide education and training on botanical biopesticide production using local resources. The activity was conducted through three systematic stages: socialization, training, and application. Socialization was held on January 18, 2026, with 25 participants including local farmers, youth representatives, and women's farmer groups. Participants learned about organic farming systems and the potential of local resources such as soursop leaves, garlic, and tobacco as biopesticide materials. The training involved hands-on demonstrations where participants actively produced biopesticides from soursop leaves and tobacco under student supervision. The application stage demonstrated biopesticide effectiveness using mealworms (Tenebrio molitor) as test insects at concentrations of 15%, 25%, and 50%. Results showed soursop-based biopesticide achieved mortality rates of 90%, 100%, and 100% respectively, while tobacco-based biopesticide achieved 100%, 100%, and 95%. This activity successfully enhanced community knowledge and practical skills in producing eco-friendly biopesticides independently. The use of easily accessible local materials helps reduce production costs and dependence on synthetic pesticides, promoting farmer independence and sustainable agricultural practices in Gumelar Village.